2023
DOI: 10.1111/srt.13298
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of 1064‐nm Q‐switched Nd:YAG laser therapy for acquired bilateral nevus of Ota‐like macules

Abstract: Background The therapeutic efficacy of laser treatments for acquired bilateral nevus of Ota‐like macules (ABNOM) varies among studies, and few studies have evaluated the factors affecting therapeutic effects. Aims To evaluate the efficacy and safety of 1064‐nm Q‐switched Nd:YAG laser (QSNYL) therapy for ABNOM and to identify the factors influencing the outcome. Methods A total of 110 patients with ABNOM were retrospectively evaluated and received two‐to‐nine treatment sessions. The effects of different factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Nhóm tuổi phổ biến của bớt Hori khác nhau tùy theo nghiên cứu. Cụ thể, nghiên cứu của Xinjun Yang và cộng sự ghi nhận nhóm tuổi 21-29 chiếm tỉ lệ cao nhất với 51,8% [7].…”
Section: đặC đIểm Chung Của đốI Tượng Nghiên Cứuunclassified
See 1 more Smart Citation
“…Nhóm tuổi phổ biến của bớt Hori khác nhau tùy theo nghiên cứu. Cụ thể, nghiên cứu của Xinjun Yang và cộng sự ghi nhận nhóm tuổi 21-29 chiếm tỉ lệ cao nhất với 51,8% [7].…”
Section: đặC đIểm Chung Của đốI Tượng Nghiên Cứuunclassified
“…Trong nghiên cứu của Trần Vũ Linh, 100% mẫu nghiên cứu là nữ [8]. Tương tự, nghiên cứu của Xinjun Yang, nữ giới chiếm tới 98,2% [7]. Như vậy, tỉ lệ mắc bệnh của hai giới còn thay đổi tùy thuộc vào thời điểm và quần thể nghiên cứu, nhưng nhìn chung đây là bệnh hay gặp phổ biến hơn ở phụ nữ, nhất là người châu Á.…”
Section: đặC đIểm Chung Của đốI Tượng Nghiên Cứuunclassified
“…Laser treatments, such as fractional carbon dioxide (FrCO 2 ) and neodymium yttrium aluminum garnet (QS Nd: YAG) lasers, can cause damage to the basal cell layer, leading to PIH 3 . Studies have found that the incidence of PIH after 532/1064 nm QS Nd: YAG laser surgery ranged from 10% to 50% in Asian patients, 4,5 with FrCO 2 laser showing a higher occurrence rate of 95.8% 6 . Once it occurs, PIH can persist for several months and have psychological impacts on patients 7 .…”
Section: Introductionmentioning
confidence: 99%